2023
DOI: 10.21037/gs-22-648
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative biliary drainage on postoperative outcome after pancreaticoduodenectomy in patients with obstructive jaundice

Abstract: Background: The role of preoperative biliary drainage (PBD) on obstructive jaundice patients is still controversial. The aim of this retrospective study is to clarify the effect of PBD on postoperative outcomes of pancreaticoduodenectomy (PD) and explore a reasonable PBD strategy for periampullary carcinomas (PAC) patients with obstructive jaundice before surgery.Methods: A total of 148 patients with obstructive jaundice who underwent PD were enrolled in this research and divided into drainage group and no-dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Nagaraj et al (16) reported two cases of central hepatectomy with liver parenchyma preservation, which increased 55 and 25% of remnant liver volumes, respectively, and avoided liver failure. Preoperative biliary drainage (PBD) is a controversial procedure (17). A previous study reported that PBD increases risk of postoperative infection and does not improve the mortality and complication rate following hepatectomy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Nagaraj et al (16) reported two cases of central hepatectomy with liver parenchyma preservation, which increased 55 and 25% of remnant liver volumes, respectively, and avoided liver failure. Preoperative biliary drainage (PBD) is a controversial procedure (17). A previous study reported that PBD increases risk of postoperative infection and does not improve the mortality and complication rate following hepatectomy (18).…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] As a result, guidelines[ 6 7 ] advise avoiding regular PBD in patients with pancreatic head cancer and obstructive jaundice, based on the findings mentioned above and other studies. [ 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%